2010
DOI: 10.1097/phm.0b013e3181e2d07c
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cervical Transforaminal Epidural Steroid Injections

Abstract: Although cervical transforaminal epidural steroid injections are used in the treatment of radicular pain, there are a number of major and minor complications reported in the medical literature. These complications are limited to retrospective studies, retrospective survey studies, case reports, and data obtained from studies evaluating the benefit of cervical transforaminal steroid injections. Thus, the data are limited in value with regard to identifying evidence-based recommendations for future research. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…The reasons to permit injections via a transforaminal route rather than the interlaminar route are to deliver the injectate directly at the target nerve, periradicularly near the ganglion of spinal nerve, to ensure that the medication reaches the region of interest in maximum concentration [5]. Because of the anatomy of the cervical spine, cervical transforaminal injections may be technically challenging, and associated with potential morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons to permit injections via a transforaminal route rather than the interlaminar route are to deliver the injectate directly at the target nerve, periradicularly near the ganglion of spinal nerve, to ensure that the medication reaches the region of interest in maximum concentration [5]. Because of the anatomy of the cervical spine, cervical transforaminal injections may be technically challenging, and associated with potential morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the anatomy of the cervical spine, cervical transforaminal injections may be technically challenging, and associated with potential morbidity and mortality [5]. Currently, procedures for cervical periradicular injections are preferentially radiographically controlled interventions [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of complication ranged from 3% to 35% in these studies. There have been case reports of more catastrophic complications, including epidural hematomas that needed to be emergently decompressed and spinal cord infarction, particularly in the setting of severe central stenosis [40]. Due to these complications and the technical difficulty of the injection, physiatrists and pain management professionals are moving away from performing this procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[37] Anterior related spine surgery helps to restore cervical lordosis, spine stabilization, decompress the nerve roots and prevent the acceleration of changes at adjacent levels. From the posterior approach multilevel and laminoforaminotomy can be done to decompress cervical nerves causing radiculopathy but in cases of open posterior aggressive dissection of subperiosteal paraspinal muscles lead to post operative morbidity which can cause disability in 18-60 pc of patients [38,40].Some of the surgeon has demonstrated the cadaver studies on anterior lateral approaches and found it as safer method and less tissues damage to reach the target point . Surgical field is so small and narrow.…”
Section: Discussionmentioning
confidence: 99%